Literacy Movement Based on Community for Sustainable Development Goals: Case Study in TBM Tanah Ombak - Devy Kurnia Alamsyah; Nur Rosita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
Literacy awareness has been arising in all community levels, started form children to adults, woman to man. How to make them literate for any aspect of life is the goal of this movement. Moreover, this awareness has been spread gradually with lining to the development of community’s engagement in their external involvement that influences their internal community. This research discusses about how literacy movement in Ruang Baca Tanah Ombak as a new phenomenon on literacy can be as a base of literacy spirit for eradicating poverty and promoting prosperity in a changing world to reach one of sustainable development goals that is education especially in Indonesia. Thus, an observation, documentation, and deep interview among the initiators, volunteers, and target group had been done in order to find how motivation strengthened the management system in problem solving, goals, and future target applied in this community. Further, the observation result, the documentation, and the interview recording were used as data to be analyzed using descriptive qualitative method. The main target of this research is to form managerial pattern of community-based literacy movement with the aim to provide model as a reference for other communities in building the literacy movement for their society. In conclusion, it is found that community-based literacy movement was a crucial matter in changing community’s understanding about the importance of literacy for human life.Keywords: Community-Based Literacy Movement, Sustainable Development Goals, Managerial Pattern, Ruang Baca Tanah Ombak